Synergistic cytotoxicity of fludarabine, clofarabine, busulfan, vorinostat and olaparib in AML cells - Valdez, Benigno C.; Yuan, Bin; Murray, David; Ramdial, Jeremy Leon; Nieto, Yago; Popat, Uday; Tang, Xiaowen; Andersson, Borje S. (Frontiers in Oncology, 2023)
Combinations of nucleoside analog(s) and DNA alkylating agent(s) are used for cancer treatment as components of pre-transplant regimens used in hematopoietic stem cell transplantation. Their efficacies are enhanced by combining drugs with different mechanisms of action, which also allows a reduction in the individual drug dosages and thus potentially in toxicity to the patient. We hypothesized that addition of SAHA and olaparib, an HDAC- and a PARP-inhibitor, respectively, to the established combination of fludarabine, clofarabine and busulfan would enhance AML cell cytotoxicity. Exposure of the AML cell lines KBM3/Bu2506, MV4-11, MOLM14 and OCI-AML3 to the 5-drug combination resulted in synergistic cytotoxicity with combination indexes < 1. Increased protein acetylation and decreased poly(ADP-ribosyl)ation were observed, as expected. Activation of apoptosis was suggested by cleavage of Caspase 3 and PARP1, DNA fragmentation, increased reactive oxygen species, and decreased mitochondrial membrane potential. The reduction in poly(ADP-ribosyl)ation was independent of caspase activation. Several proteins involved in DNA damage response and repair were downregulated, which may be contributing factors for the observed synergism. The increased phosphorylation of DNAPKcs suggests inhibition of its kinase activity and diminution of its role in DNA repair. A similar synergism was observed in patient-derived cell samples. These findings will be important in designing clinical trials using these drug combinations as pre-transplant conditioning regimens for AML patients.